If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 + 42 = 0 Reorder the terms: 6 + 42 + 2x = 0 Combine like terms: 6 + 42 = 48 48 + 2x = 0 Solving 48 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 2x = 0 + -48 Combine like terms: 48 + -48 = 0 0 + 2x = 0 + -48 2x = 0 + -48 Combine like terms: 0 + -48 = -48 2x = -48 Divide each side by '2'. x = -24 Simplifying x = -24
| -24+8x=6x-4(x-6) | | 6t(11+5)=0 | | 5-3x=-10 | | 3x+4x+5x-8x+8=12 | | b^2=100 | | -3(1t+5)+(4t+2)=8 | | x=-2(80)+300 | | 4(10x-7)=292 | | 7p-4=1-3p | | 3/5x+8=-12 | | 11m-8=12 | | 3y=800-4(-2y+300) | | 6-4(2x-1)= | | 3x/8=x/2-1 | | 3(2m-4)=18 | | -9b-3=-3[b+2] | | 2(2t-3)=5(2t+3) | | 81=45+5r | | y=4-4(2)+1 | | 21=2x^2+2 | | 2x^2-12y-80=0 | | 5x+(-5x-7)=-3 | | 20+(3*5)=7n | | y=9-12+1 | | 3x-7+2x=23 | | 11n-1=10 | | 12x+1=22 | | y=16-4(4)+1 | | 3x^2+x=6 | | 21(x+8)-12(9+2x)=10(2x+4) | | 1/2+5/x | | (14-8)*9=9m |